Exploring Asymmetrical Relations and Diverse Processes of Enslavement in the Aviation Industry of Nigeria - Samuel, Samuel; Paul, Kinikanwo-Chimenim (LPPM STIE Krakatau, 2025)
Purpose: This paper analyzes the impact of political patronage, bureaucratic corruption, and foreign capital dependency on labor conditions within Nigeria’s aviation industry. Employing clientelism and dependency theory, it explores how these factors contribute to institutional inefficiency and diminished worker welfare. Research Methodology: This study employs a case study approach, examining agencies such as the Federal Airports Authority of Nigeria (FAAN) and analyzing secondary data to investigate the effects of liberalization policies, casualization, outsourcing, and labor issues within the sector. Results: The study found that political patronage and corruption contribute to inefficiency and poor service delivery within aviation agencies. Liberalization policies were associated with increased job insecurity, stress, and gender inequality, particularly among contract workers and ground staff. Conclusions: This paper concludes that improvements in worker welfare and sector competitiveness within Nigeria’s aviation industry require merit-based recruitment, strengthened labor laws, formal contracts, gender inclusion, and local ownership. Limitations: This study is limited by its reliance on secondary data and its focus on Nigeria, potentially restricting generalizability to other regions. Contribution: The study offers policy recommendations aimed at improving recruitment practices, labor rights, and gender equality, thereby contributing to both theoretical and practical solutions for Nigeria’s aviation sector